Assessing possible economic or operational benefits of class 3 webs without stiffeners vs class 4 webs with stiffeners in steel plate girders - Tafadzwa, Chikosha Franklin (Department of Civil Engineering, 2022)
The aim of this research was to identify a possible range where the use of deep I-plate girders primarily under bending stresses with thick web plates and no web stiffeners has economical or operational benefits than adoption of plate girder cross-sections with slender web plates reinforced with intermediate transverse stiffeners. The research focuses mainly on optimisation for bending moment resistance. Shear capacities of the cross-sections were also computed and compared because shear forces share a close relationship with bending moments being a derivative of the moment. The idea was that upon exhausting the capacity of the largest available rolled I-section, designers should not always tend to lean towards sections with slender web as is common practice encouraged by design standards to get the highest moment carrying capacity. Design codes or standards adopted by different countries and sometimes regions provide structural designers with guidelines on acceptable design practice. The latest South African design standards encourage the use of thin web plates with stiffeners to guard against premature buckling of the web whilst realising high bending moment resistance. This is due to the increased lever arm and having more material in the flange plates as explained in SASCH (2016). Though setting an upper limit on web slenderness βw, the South African steel design standard, SANS10162-1 allows designers to ignore the limit if calculations prove that buckling of the compression flange into the web will not occur under factored load levels. SASCH (2016) alludes to the possibility of there being benefits that can be realised from using thicker web plates than the theoretically recommended ones but it does not give a comprehensive insight as to the nature and extent of those benefits. As shown in the following chapters, not much research has been done to assess the benefits of adopting compact webs in plate girders. For a given cross-section area, different geometrical cross-section configurations were compared in an iterative process. The parameters under investigation were the moment resistance and shear carrying performance to mass ratios. Other design parameters of the elements were not to be compromised following recommended guidelines in the South African steel design standard, SANS10162-1. Additional knowledge gathered from research work detailed in the literature study was incorporated in the optimisation process but guidelines from SANS10162-1 took precedence. The exercise showed that for cross-section area requirements below 35.6x103mm2 to carry moments, wholly class 3 sections provide a competitive alternative to sections with class 4 webs and flanges below class 3 classification. They resist a lesser moment, but the differences are of small magnitudes. The class 3 sections showed significant improvements in terms of shear capacity. Over larger spans, sections with class 4 webs with intermediate transverse stiffeners and of similar mass per unit length become heavier and more expensive because of the increase in the number of stiffeners. The labour requirements and consumables for fabrication also increase because of the stiffener requirements for sections with class 4 webs as shown in the cost estimates.